Negotiating left-hand and right-hand bends: a motorcycle simulator study to investigate experiential and behaviour differences across rider groups - Crundall, Elizabeth; Crundall, David; Stedmon, Alex W. (PLoS, 2012)
Why do motorcyclists crash on bends? To address this question we examined the riding styles of three groups of motorcyclists on a motorcycle simulator. Novice, experienced and advanced motorcyclists navigated a series of combined left and right bends while their speed and lane position were recorded. Each rider encountered an unexpected hazard on both a left- and right-hand bend section. Upon seeing the hazards, all riders decreased their speed before steering to avoid the hazard. Experienced riders tended to follow more of a racing line through the bends, which resulted in them having to make the most severe changes to their position to avoid a collision. Advanced riders adopted the safest road positions, choosing a position which offered greater visibility through the bends. As a result, they did not need to alter their road position in response to the hazard. Novice riders adopted similar road positions to experienced riders on the left-hand bends, but their road positions were more similar to advanced riders on right-hand bends, suggesting that they were more aware of the risks associated with right bends. Novice riders also adopted a safer position on post-hazard bends whilst the experienced riders failed to alter their behaviour even though they had performed the greatest evasive manoeuvre in response to the hazards. Advanced riders did not need to alter their position as their approach to the bends was already optimal. The results suggest that non-advanced riders were more likely to choose an inappropriate lane position than an inappropriate speed when entering a bend. Furthermore, the findings support the theory that expertise is achieved as a result of relearning, with advanced training overriding ‘bad habits’ gained through experience alone.